BDNF Alleviates Microglial Inhibition and Stereotypic Behaviors in a Mouse Model of Obsessive-Compulsive Disorder - Luo, Yuchong; Chen, Xiao; Wei, Chunren; Zhang, Hongyang; Zhang, Lingyi; Han, Lu; Sun, Ke; Li, Boxing; Wen, Shenglin (Frontiers in Molecular Neuroscience, 2022)
Obsessive-compulsive disorder (OCD) is a severe mental illness characterized by obsessions and compulsions. However, its underlying mechanisms remain to be elucidated. Recent studies have suggested that neuroimmune dysregulation is involved in the pathogenesis of OCD. To investigate the role of microglia in this disorder, we established a pharmacological mouse model by using the serotonin (5-HT) 1A/1B receptor agonist RU24969 to mimic monoamine dysregulation in OCD, and we examined the morphological and functional alterations of microglia in this model. We found that RU24969 treatment led to compulsive circling behavior in mice. Strikingly, we found that the density and mobility of microglia in the prelimbic cortex were much lower in RU24969-treated mice than in control mice. Moreover, the expression of cytokines and chemokines, including BDNF, IL-1β, IL-6, TNFα, CD80, CD86, MHC-I, and MHC-II, also decreased in RU24969-treated mice. Importantly, we found that injection of BDNF or induction of BDNF expression by trehalose completely reversed microglial dysfunction and reduced stereotypic behavior. These results indicate that microglial dysfunction is closely related to stereotypic behaviors in our mouse model of OCD and that BDNF could be an effective treatment for stereotypic behaviors.